The microbial ecology of sulphidogenic lignocellulose degradation - Clarke, Anna Maria (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
Acid mine drainage is a well known environmental pollutant, not only in South Africa, but throughout the world, and the use of microbial processes in the treatment of these wastes has been the subject of investigation over past decades. Lignocellulose packed-bed reactors have been used in passive treatment systems, and, although effective initially, they show early decline in performance while the packing material remains largely un-utilized. Little is known about this phenomenon which remains a severe constraint in the development of efficient passive mine water treatment systems. It has been proposed that the degradation pathways of the complex lignocellulose substrate may be limited in some way in these systems during the manifestation of this effect. This study has addressed the problem using a molecular microbial ecology methodology in an attempt to relate trophic functions of the microbial population to the physico-chemical data of the system. A field-scale lignocellulose packed-bed reactor located at Vryheid Coronation Colliery (Northern Kwa-Zulu Natal province, South Africa) was monitored for six years and the results showed the classic profile of performance decline related to a slowdown in sulphate reduction and alkalinity production. The reactor was decommissioned , comprehensive samples were collected along the depth profile and the microbial populations investigated by means of 16S rRNA gene methodology. The population was found to include cellulolytic Clostridia spp., CytophagaIFlavobacterlBacteroidetes, Sphingomonadaceae and as yet uncultured microorganisms related to microbiota identified in the rumen and termite gut. These are all known to be involved as primary fermenters of cellulose. Oesulphosporosinus was present as sulphate reducer. A comparison of substrata sampling and population distribution suggested that spatial and temporal gradients within the system may become established over the course of its operation. Based on these findings, a laboratory-scale reactor was constructed to simulate the performance of the packed-bed reactor under controlled experimental conditions. The laboratory-scale reactor was operated for 273 days and showed comparable performance to that in the field in both biomolecular and physicochemical data. Clearly defined trophic niches were observed. These results suggested that a sequence of events does occur in lignocellulose degradation over time. Based on the spatial and temporal column studies, a descriptive model was proposed to account for these events. It was found that fermentative organisms predominate in the inlet zone of the system using easily extractable compounds from the wood, thus providing feedstock for sulphate reduction occurring in the succeeding compartments. Production of sulphide and alkalinity appears to be involved in the enhancement of lignin degradation and this, in turn, appears to enhance access to the cellulose fraction. However, once the readily extractables are exhausted, the decline in sulphide and alkalinity production leads inexorably to a decline in the overall performance of the system as a sulphate reducing unit operation. These observations led to the proposal that with the addition of a limited amount of a readily available carbon source, such as molasses, in the initial zone of the the reactor, the ongoing generation of sulphide would be sustained and this in turn would sustain the microbial attack on the lignocellulose complex. This proposal was tested in scale-up studies and positive results indicate that the descriptive model may, to some extent, provide an account of events occurring in these systems. The work on sustaining lignocellulose degradation through the maintenance of sulphate reduction in the initial stages of the reactor flow path has led to the development of the Degrading Packed-bed Reactor concept and that, has subsequently been successfully evaluated in the field.
Keywords: Microbial ecology; Lignocellulose; Sulfides; Lignin; Lignocellulose -- Biodegradation; Mines and mineral resources -- Waste disposal; Acid mine drainage